Streams of Latin American Protestant Theology - Gladwin, Ryan R. (Brill research perspectives in theological traditions, 2020)
Although church historians often call the 19th century the Great Century of Protestant mission, for Latin America it was the 20th century that was the great century of Protestant growth and expansion. The 20th century witnessed vast societal changes and the realization of systemic poverty and injustice as well as the exponential growth, pentecostalization, and diversification of Latin American Protestantism. Latin American Protestant Theology emerged during this century of change. This text provides an introduction to Latin American Protestant Theology by engaging its dominant theological streams (Liberal, Evangelical, and Pentecostal) and how they understand themselves through the lens of mission. The text offers both a critique of the Christendom cartography that is dominant in Latin American Protestant Theology as well as suggestions for how to move towards a transformative theology of mission. The primary intention of this text is to offer an informed outline and analysis of the theological landscape of Latin American Protestantism. The secondary intention of this book is to note the contributions as well as deficiencies of the streams of LAPT in the hope to signal a possible path towards the development of an integral, transformative, contextual, and decolonial theological voice.